Ecotourism Management of Green Leaves of Mangroves Perspective of Maqāṣid al-Sharī'ah Yusuf al-Qardawi - Masitoh, Imas; Rahmawati, Lilik; Elbarqi, Muhammad Nur Sholeh (Al-Tijary, 2023)
Insufficient public awareness and comprehension of coastal natural resource management Limited public education, community characteristics, and economic pressures frequently lead to coastal communities causing harm to the coastal environment. The utilization of coastal resources can be achieved through the implementation of coastal tourism. Ecotourism is a novel form of alternative tourism that has emerged as a response to the traditional model of tourism. This traditional model often exploits natural resources without considering their long-term sustainability and disregards the well-being of local populations. This study employs a qualitative research methodology that utilizes a descriptive approach, drawing upon both primary and secondary data sources. This study demonstrates a correlation between the environment and religion. Maqāṣid al-syarī'ah represents the fundamental principles of Islamic teachings that guide the creation of laws with a focus on the welfare and advantage of humanity. Conducting economic activities must align with the maqāṣid al-syarī'ah, which are the objectives of Islamic law, aimed at preserving al-mabadi al-khamsah, the five essential principles. The name of the place is "Green Leaf Mangrove". Ecotourism management encompasses initiatives focused on the preservation of mangroves, coral reefs, and turtles, as well as activities promoting conservation education, beach cleaning, and garbage processing. These programs are designed to align with the concepts of maqāṣid al-syariah, ensuring environmental management in accordance with Islamic values. Based on the results, this study has an implication that will help policy makers to improve and develop ecotourism quality while considering strategy for integrating tourism and environmental protection.